Nikah Beda Agama dan Implementasinya di Indonesia - Marwinata, Pepy; Hakim, Muhammad Nur Rizal (Sharia Journal and Education Center Publishing, 2025)
The phenomenon of interfaith marriage in Indonesia remains a complex debate between religious law, state law, and human rights. Law No. 1 of 1974 on Marriage stipulates that a marriage is valid if it is conducted according to the laws of each religion and belief, implying that interfaith marriage has no clear legal basis in Indonesia. However, in reality, interfaith marriages continue to occur in various ways, either through the conversion of one of the parties or through registration abroad. This article aims to analyze the legal regulations on interfaith marriage in Indonesia, their implementation in the field, and the tension between religious values, national law, and freedom of religion. This study uses a normative juridical approach by examining legislation, court decisions, and Islamic legal views. The results of the study show that the prohibition of interfaith marriage is based on theological and normative reasons, but in practice there is still room for compromise, which shows disharmony between religious law and state law. Therefore, a more humanistic and equitable legal approach is needed without neglecting the principles of sharia and public morality.